KARAKTERISTIK LAPIS ASPAL BETON (LASTON) YANG MENGGUNAKAN MIKROENKAPSULASI SEBAGAI AGREGAT HALUS DENGAN BAHAN PEREMAJA SOLAR - , ELIZA WINASRIKA A, Ir. Heru Budi Utomo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Self healing materials is a material that can repair the damage itself, obtained by implanting fluxing materials (diesel) to material (pumice stone). Asphalt concrete (Laston) is a mixture of fine aggregate and coarse aggregate, and filler with asphalt in high heat temperature. Laston in this research using a mixture of crushed stone aggregate mixed with microencapsulation. This research aims to determine how to manufactured and produce microencapsulation, utilizing microencapsulation as the manufactured of asphalt concrete aggregate mix, knowing the nature and characteristics of laston by marshall test, and knowing the characteristic of aspalth concrete using microencapsulation as fine aggregate. The first step of manufacturing process is making the core, then coating process, and making a shell or wall process. The next step is marshall testing to obtain optimum bitumen content (KAO). After the KAO obtained, making the specimen with and without microencapsulation with optimum bitumen content that has been obtained, then testing marshall again. In the testing marshall to obtain optimum bitumen content failed or otherwise canât be obtained the optimum bitumen content, so use the bitumen content in general. The test results showed of the specimen with a mixture of microencapsulation has a small value than the stability of the test specimen microencapsulation.